Cloud Cover Feedback Moderates Fennoscandian Summer Temperature Changes Over the Past 1,000 Years - Giles Young (Geophysical Research Letters, 2019)
Northern Fennoscandia has experienced little summer warming over recent decades, in 24 contrast to the hemispheric trend, which is strongly linked to greenhouse gas emissions. A likely25 explanation is the feedback between cloud cover and temperature. We establish the long- and26 short-term relationship between summer cloud cover and temperature over Northern27 Fennoscandia, by analysing meteorological and proxy climate data. We identify opposing28 feedbacks operating at different timescales. At short timescales, dominated by internal29 variability, the cloud cover-temperature feedback is negative; summers with increased cloud30 cover are cooler and sunny summers are warmer. However, over longer timescales, at which31 forced climate changes operate, this feedback is positive, rising temperatures causing increased32 regional cloud cover and vice versa. This has occurred both during warm (Medieval Climate33 Anomaly and at present) and cool (Little Ice Age) periods. This two-way feedback relationship34 therefore moderates Northern Fennoscandian temperatures during both warm and cool35 hemispheric periods.